2021
DOI: 10.3233/jad-210173
|View full text |Cite
|
Sign up to set email alerts
|

Grey Matter Loss at Different Stages of Cognitive Decline: A Role for the Thalamus in Developing Alzheimer’s Disease

Abstract: Background: Alzheimer’s disease (AD) is characterized by cognitive impairment and large loss of grey matter volume and is the most prevalent form of dementia worldwide. Mild cognitive impairment (MCI) is the stage that precedes the AD dementia stage, but individuals with MCI do not always convert to the AD dementia stage, and it remains unclear why. Objective: We aimed to assess grey matter loss across the brain at different stages of the clinical continuum of AD to gain a better understanding of disease progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 65 publications
6
45
0
1
Order By: Relevance
“…Nevertheless, we found that the MMSE scores were correlated with almost all the significant clusters, thereby suggesting the role of these regions in global cognition. This finding is in line with many studies investigating the brain anatomical correlates with global cognition (25)(26)(27)(28)(29)(30). The precuneus is a core of the DMN, and this result is also in line with other published reports on vascular cognitive impairment (51)(52)(53).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nevertheless, we found that the MMSE scores were correlated with almost all the significant clusters, thereby suggesting the role of these regions in global cognition. This finding is in line with many studies investigating the brain anatomical correlates with global cognition (25)(26)(27)(28)(29)(30). The precuneus is a core of the DMN, and this result is also in line with other published reports on vascular cognitive impairment (51)(52)(53).…”
Section: Discussionsupporting
confidence: 92%
“…These silent lesions represent physical dysconnectivity, compromised coordination between interconnected gray matter regions, and progressive atrophy itself. We know that cortical gray matter integrity is the neuroanatomical basis of large-scale brain networks that support human behaviors and cognition, and mounting evidence links gray matter atrophy to cognitive impairment (25)(26)(27)(28)(29)(30). However, it is unclear that whether and to what extent HHT may affect the DMN gray matter morphometry.…”
Section: Introductionmentioning
confidence: 99%
“…The distinction between AD and early FTD can also be challenging on clinical grounds. There is evidence of relatively selective thalamic nuclei involvement along the clinical continuum of AD [76]. Post-mortem studies have shown preferential involvement of the anterior thalamic nuclei with relative sparing of the medial dorsal nuclei even in the later stages [77], which is particularly interesting given our contrary finding of mediodorsal nuclei atrophy in FTD.…”
Section: Discussionmentioning
confidence: 71%
“…Cross-sectional studies have shown that cognitive decline at different stages of the Alzheimer’s disease (AD) correlate with gray matter loss ( Van de Mortel et al, 2021 ; Wu et al, 2021 ). At late stages of AD, a widespread reduction in brain volume was consistently found in the hippocampus, temporal pole, medial- and inferior temporal cortex, precuneus, parietal lobe and cerebellum ( Chapleau et al, 2016 ; Dicks et al, 2019 ; Kang et al, 2019 ; Kunst et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%